Effects of urbanization on homestead size and tree species diversity among farmers in Comilla district: Homestead size and tree species diversity among farmers in Comilla - Mahbub, S U B; Naher, N; Helal, M G J; Marma, L; Amin, M R; Talucder, M S A; Khan, A U (Bangladesh Journal of Agriculture, 2025)
Modernization plays a crucial role in socio-economic development globally and in Bangladesh. Agroforestry practices are increasingly adopted to support sustainable livelihoods. This study examines the impact of urbanization on homestead size and tree species diversity in Debidwar Upazila, Comilla district. Data were collected through structured interviews with 90 randomly selected farmers from six villages between January and June 2018. Results indicate that most respondents in traditional and semi-modern areas were middle-aged with secondary education, while modern areas had more individuals with education beyond the secondary level. Family sizes were mostly medium (4–6 members), and income levels were moderate across all areas. Agriculture remained the primary occupation in traditional and semi-modern zones, whereas service sector jobs dominated in modern areas. Homestead sizes were generally medium in traditional and semi-modern areas but smaller in modern areas. Traditional agroforestry systems supported greater tree species diversity (18 species) compared to modern areas (11 species). Common tree species included mango (630), coconut (311), betel nut (240), and jackfruit (206). Key challenges such as transportation issues, unemployment, and economic difficulties were prevalent. Urbanization showed significant positive correlations with education, occupation, income, homestead size, tree species, and local problems, but no significant correlation with age or family size. The study concludes that urbanization has led to a notable reduction in homestead size and tree species diversity in the region. Bangladesh J. Agri. 2025, 50(1): 117-131